Legal Protection for Legitimate Owners in Disputes Over Dual Certificate Ownership Due to Unlawful Acts - Sari, Nurmila; Arifullah, Achmad (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. This study aims to analyze the legal protection provided to legitimate owners in dealing with disputes over ownership of duplicate certificates and the legal remedies that can be taken in response to such unlawful acts. The research approach uses a normative juridical method by reviewing laws and regulations, court decisions, and related legal literature. The analysis refers to several key regulations, namely Law Number 5 of 1960 concerning Basic Agrarian Regulations (UUPA), which regulates land ownership rights and dispute resolution mechanisms; Law Number 4 of 1996 concerning Mortgage Rights; and Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. In addition, legal protection is also based on the provisions of the Civil Code (KUHPerdata), specifically regarding unlawful acts (Article 1365 of the KUHPerdata), which allows legitimate owners to file lawsuits for compensation and cancellation of duplicate certificates. The results of the study indicate that legal protection for legitimate owners still faces obstacles such as complex land administration bureaucracy and the potential for corruption, as well as weak coordination between relevant institutions. Therefore, it is necessary to strengthen legal mechanisms by increasing transparency and accuracy in land administration, as well as strict law enforcement against unlawful acts that result in the issuance of duplicate certificates. Legitimate owners can pursue civil and criminal legal remedies, including filing lawsuits for unlawful acts, to obtain legal certainty and restitution of their rights. This study provides strategic recommendations for the government and relevant institutions in improving the land administration system and strengthening legal protection to achieve justice for legitimate landowners and reduce duplicate certificate disputes in Indonesia. Keywords: Disputes; Dual Certificates; Legal Protection.